Effectiveness of Criminal Law Enforcement against Corporations: Procedural Analysis and Mechanisms of Cross Country Criminal Justice - Agussalim A Gadjong (Faculty of Law, Universitas Pekalongan, 2025)
The regulation on regional heads in Indonesia, as stipulated in Article 18 of the 1945 Constitution of the Republic of Indonesia and the Regional Government Law, prioritizes the principles of democracy and regional autonomy, with an emphasis on direct elections by the people to ensure accountability and legitimacy. However, the appointment of acting regional heads (Pj) that does not involve direct community participation has raised criticism regarding transparency, legitimacy, and lack of public participation. This study aims to formulate regulations related to the appointment of acting regional heads during the transition period to realize responsive law. This study is a normative legal study that prioritizes conceptual and legislative approaches. The results of the study confirm that a responsive legal approach can be a solution, by emphasizing the importance of legal flexibility to respond to community needs, as well as increasing openness, participation, and accountability in the process of appointing Pj. The appointment of Pj by the President and the Minister of Home Affairs without community participation risks worsening the centralization of power, reducing the role of community participation, and damaging the essence of democracy. Therefore, more inclusive reforms are needed in this process to strengthen a government system that is more responsive to community aspirations. Therefore, revisions to the Regional Government Law and the Regional Election Law are very necessary to ensure a more transparent, accountable, and better community involvement in the appointment process for Acting Heads.